2015
DOI: 10.1155/2015/741618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature Variation on Vibration Monitoring of Prestressed Concrete Girders

Abstract: The effect of temperature variation on vibration monitoring of prestressed concrete (PSC) girders is experimentally analyzed. Firstly, vibration features such as autoregressive (AR) coefficient, correlation coefficient of power spectral density (CC of PSD), natural frequency, and mode shape are selected to estimate the effect of temperature variation on vibration characteristics of PSC girders. Secondly, vibration experiments on a lab-scale PSC girder are performed under the condition of temperature variation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Simultaneously, actual structures are often affected by environmental factors, such as temperature variations and weather changes, which have an impact on the performance of damage identification. Studies shown that the temperature variations will cause the vibration features of structures, which make inaccurate damage identification (Huynh et al, 2015 and Huang et al, 2020a). Considering the temperature variation, the relationship between the ambient temperature and Young’s modulus is shown in Figure 2 (Huang et al, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, actual structures are often affected by environmental factors, such as temperature variations and weather changes, which have an impact on the performance of damage identification. Studies shown that the temperature variations will cause the vibration features of structures, which make inaccurate damage identification (Huynh et al, 2015 and Huang et al, 2020a). Considering the temperature variation, the relationship between the ambient temperature and Young’s modulus is shown in Figure 2 (Huang et al, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…This is further complicated by the global nature of vibration monitoring because other types of damage and change of boundary conditions can result in changes in natural frequencies. Moreover, natural frequencies can vary significantly due to environmental changes and lack of ideal supports; one study reports a 6% change, whereas another reports up to 18% change . In comparison, changes in frequency due to prestress losses are insignificant and may not be detected …”
Section: Vibration Methodsmentioning
confidence: 99%
“…For vibration-based techniques, the methods have been successfully applied to determine prestressing force cable using measured frequencies [5,6]. It is found that measured natural frequencies were significantly changed under environmental temperature variations [7,8].…”
Section: Introductionmentioning
confidence: 99%